2019
DOI: 10.3390/ijerph16173171
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Type 2 Diabetes Mellitus after Bariatric Surgery: Fact or Fiction?

Abstract: Although type 2 diabetes mellitus (T2DM) has been traditionally viewed as an intractable chronic medical condition, accumulating evidence points towards the notion that a complete remission of T2DM is feasible following a choice of medical and/or surgical interventions. This has been paralleled by increasing interest in the establishment of a universal definition for T2DM remission which, under given circumstances, could be considered equivalent to a “cure”. The efficacy of bariatric surgery in particular for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 128 publications
(156 reference statements)
1
36
1
3
Order By: Relevance
“…However, gender and baseline BMI in non-Asian ethnicities could not predict diabetes remission. The results of our study are comparable with several other studies suggesting that gender and BMI had no effect on diabetes remission [6].…”
Section: Discussionsupporting
confidence: 92%
“…However, gender and baseline BMI in non-Asian ethnicities could not predict diabetes remission. The results of our study are comparable with several other studies suggesting that gender and BMI had no effect on diabetes remission [6].…”
Section: Discussionsupporting
confidence: 92%
“…Recommendations indicate bariatric surgery as the preferred treatment for T2D in class III obese (body mass index (BMI) ≥40) subjects, with consideration of surgery for class II obese individuals (BMI 35-39.9) with inadequate control of hyperglycemia. T2D remission rates might vary depending on the surgical procedure, studied population, and definition of T2D remission [177].…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…This study was the first documentation of bariatric surgery as a potential "cure'' for T2DM. 7 The researchers also observed that younger patients and those with a shorter duration of T2DM were more likely to go into remission postoperatively. 8 More evidence supporting the role of bariatric surgery in the treatment of T2DM emerged in the early 2000s.…”
mentioning
confidence: 95%